Effect of reduced doses of a post-emergence graminicide to control Avena sterilis L. and Lolium rigidum G. in no-till wheat under Mediterranean environment - Barros, José (2008)
The study was carried out over 2 years (2004–2005 and 2005–2006) in a private farm in the Alentejo region (E´ vora), in the south of Portugal where rainfed wheat is sown after the beginning of the winter rainfall season. The wheat crop used for this study was established using no-till, as this technology provides the necessary machine-bearing capacity of the soil to assure post-emergence application of herbicides at different weed development stages. A mixture of clodinafop+cloquintocete was applied using three different dosages and volumes on two dates. The results indicate that lower herbicide doses than those recommended by the manufacturer were sufficient to achieve a high Avena sterilis L. and Lolium rigidum G. control efficiency and consequently potential grain yield, when the treatments were carried out on an early application date (beginning of tillering). When the herbicide application was delayed (complete tillering) it was necessary to increase the herbicide dose in order to achieve the highest grain yield. There was a positive and significant correlation between weed control efficiency and grain yield, but the respective correlation coefficient was not very high. This is because at the first application stage, both weeds and crop were more sensitive to the herbicide and consequently there was some crop phytotoxicity caused by the herbicide when its concentration increased. Weed reinfestation was low for both application dates, indicating that lower herbicide doses than the recommended ones can be used for satisfactory control of A. sterilis L. and L. rigidum G.